Obtaining of zirconium catalysts based on pillared clays for peroxide oxidation of 4-nitrophenol - Kalmakhanova, Marzhan (2019)
Natural resources, including abundant and cheap natural clays in the southern regionare one of the main wealth of the Republic of Kazakhstan. The chemical industry in Kazakhstanis being developedrapidly in recent years and there is an urgent need to find solutions for the treatment of wastewaters. This work aims to explore natural clays for the synthesis of low-cost pillared clays that can be used as catalysts in oxidation technologies for the treatment of wastewaters. Nitrophenols are commonly found in many types of wastewaters (plastic, pharmaceutical, paper or pesticide production).The purification of suchspecific wastewater according to classical schemes does not always ensure a safe level of pollution in waters discharged into water ponds. Thus, further development of the chemical industry will inevitably be associated with the need for more effective disposal of wastewater containing toxic products. 4-nitrophenol was used as a representative model compound in catalyst screening studies.Catalysts based on pillared clays modified with Zr4+cations were synthesized from natural clays of Karatau and Kokshetau deposits and investigated for the catalytic wastewater peroxide oxidation (CWPO) of 4-nitrophenol (4-NP) at 323 K. Pillared clays with Zr4+ showed the higher catalytic activity in the removal of 4-NP and Total organic carbon (TOC) by CWPO and selectivity for the formation of CO2 and H2O than natural clays.The best 4-NP and TOC conversion results were obtained by using the pillared clay from Karatau deposit as a catalyst. A complete removal of the contaminant was achieved after 2 hours with 97.3 % conversion.